Modular Permanent Magnet Synchronous Machine with Low Space Harmonic Content - Keyi Wang; Heyun Lin (Energies, 2020)
Modularity technique is desirable in large permanent magnet synchronous machines (PMSMs) because it facilitates manufacture, assembly, and maintenance. Although the PMSMs with fractional-slot concentrated windings (FSCWs) allow their stators to be modularized, they usually suffer from high nonworking space harmonic content. The PMSMs with various reported two-slot pitch windings (TSPWs) show much lower nonworking space harmonic content, but they do not support stator modularity. This paper proposes a modular PMSM with a special dual three-phase (DTP) TSPW, which exhibits quite low nonworking space harmonic content. First, the topology of the proposed machine is described in detail. Then, the mechanism of reducing the nonworking space harmonic content of the machine is expounded through winding magnetomotive force (MMF) analysis. Finally, the electromagnetic characteristics of a specific proposed modular PMSM and a conventional modular PMSM with DTP-FSCW are compared by finite element method (FEM), in terms of electromotive force (EMF), armature reaction field, torque performance, efficiency and power factor. The FEM results demonstrate that the proposed machine can realize low space harmonic content while retaining stator modularity.